New characteristics of management. Characteristics of planning at a managerless company – a case study of a managerless company - Håkansson,Vera (2018)
The increased development phase in society puts pressure on companies being more adaptable to the changing environments. Some companies have answered to this challenge by organizing themselves as managerless, to create shorter information flows and a more rapid innovation process. With this managerless structure a set of questions arise in relation to the classic management theories about the different functions that managers perform in order to create effective and successful companies. This study aims to explore how the function of planning is performed at a managerless company, and the characteristics of planning when it is not performed by a manager. The purpose is also to understand how this differs from planning at a manager-led company. To achieve this, a case study with qualitative in-case interviews was applied in order to gather deep insight about the planning process in relation to the managerless structure. Robbins and Coulter’s (2016) definition of planning is applied throughout the study in order to create a sense of clarity in a field of many definitions and concepts. This is discussed together with other theories regarding planning and leadership. The conclusion reached in this thesis is that planning is performed by everyone in the organization, in different ways and on different levels. The characteristics of the planning process is: driven by ambition, dynamic, collectiveness, personal responsibility and accountability. The overall plan, at the managerless company studied in this case, is less detail-oriented than at a manager-led company, as described by the theories used in this thesis.
Keywords: planning; managerless companies; managerial functions; collective leadership; shared leadership; distributed leadership; case study